Avaliação do desempenho educacional no Ceará - Benevides, Alesandra de Araújo (2016)
The economics of education has a vast literature, intensified from the 1990s, we rarely see in other economic areas in Brazil. Among the major concerns of the researchers are seeking to understand what makes a student more skills and knowledge than others at the end of a cycle. This thesis focuses primarily on the academic performance of students from Ceará and sheds light on three specific issues that contribute to understand the gear of educational quality. First, it was observed in 2011 that students of the 5th grade of the Fortaleza municipal school system do well on standardized test Prova Brasil when they have good grades (up to five) in school. Although the relationship between school performance and school grades is not causal and many variables can influence this result, this positive impact is quite robust, even when taking into account the characteristics of the student and teacher, director, and school characteristics. Somehow, this result points that the public school teacher does not easily approves students without proper charges in relation to the content taught. On the second point, I tried to find what the actual influence of school transfers on math performance for students of the High School of Ceará. According to the literature, there are two possible and ambiguous effects for this variable. One effect can be positive if the purpose of the change is to seek a better school, which provides greater opportunity for the student. But it can also have a negative impact when the reasons for the change include bad behavior, difficulty adapting, among others reason. In general, this student mobility generates no significant impact. However, when decomposition is made mobility variable separating between students who changed town and only those who changed schools, remaining in the same town, it was found that the mobility intramunicipal reduces the student's performance. The third and final point sought to investigate why students of military public schools stand out so positively on standardized tests such as SPAECE and ENEM. It can be argued that the performance of these students is overvalued if their previous performance is not taken into account. At least 50% of the academic performance of military difference to civilian students is due to the fact that those were already good students earlier. It's the inertial condition of knowledge accumulation. What is observed, after all the analysis and evaluation of the different variables that impact performance, is that there is no single, unambiguous way the get quality education. The school enviroment matters, the teacher is a key to better learnig, the school’s efficient management and services it provides to the community, the financial and infrastructure resources, the effective participation of parents in the learning process, among many other factors.